Zero Staff Assaults in the Psychiatric Emergency Room: Impact of a Multifaceted Performance Improvement Project. (January 2021) - Okundolor, Sonny I.; Ahenkorah, Florence; Sarff, Laura; Carson, Nora; Olmedo, Alirio; Canamar, Catherine; Mallett, Sheila
INTRODUCTION: Our psychiatric emergency room (ER) averages 18 patient-to-staff physical assaults annually, with some incidents resulting in multiple injuries.AIMS: The purpose of this performance improvement project was to develop, implement, and evaluate a multifaceted approach to reducing the number of physical assaults on staff.METHODS: We assessed the impact of these bundled interventions on staff assault rate: (1) increasing behavioral response team drills, (2) implementing shift doses, (3) screening for patients' risk for violence, (4) posting signage to communicate patients' violence propensity (Golden Hand), (5) implementing mitigating countermeasure interventions, (6) conducting postassault debriefing, and (7) providing postassault support. Psychiatric ER nurses completed questionnaires measuring their perceived self-efficacy in managing patients with a propensity for violence before, during, and after the bundled interventions. Physical assaults on staff were recorded and tracked monthly from May 2016 to September 2018 through a retrospective review of the hospital's online incident report system.RESULTS: Staff perceived self-efficacy increased from 78% to 95% after attending at least two behavioral response team drills. The Golden Hand signage was rated useful as it flagged and communicated the presence of high-risk patients. Shift dose was evaluated as an informative tool and manageable at ≤5 minutes. The violence-screening tool was considered more accurate in identifying patients with violent tendencies than standard assaultive precautions. Physical assaults on staff by patients decreased to zero in our psychiatric ER, which was sustained for a year.CONCLUSIONS: This innovative, multifaceted, bundled approach provides an opportunity for nurse leaders to promote workplace safety while improving staff engagement and empowerment.